(untitled) (Revista da Faculdade de Direito, Universidade de São Paulo, 2004)
A reflection concerning the concept and the legal nature of free software, beyond the free works, similarities and differences between the free programs and its antagonism; the thought of Hannah Arendt concerning the questioning on what we are doing (on Earth) are subjects considered by the author.